Greta Thunberg and the transnational youth elite in global climate politics : myth or reality? - Orsini, Amandine; Kang, Yi Hyun ; 0000-0001-9991-2496 (Environmental Politics, 2025)
Greta Thunberg has gained increasing attention in global climate politics, in particular since the Fridays for Future movement she initiated in 2018. Attention has also come with criticism, denouncing her for being part of a transnational youth climate elite made up of privileged youth. However, does such an elite really exist, and what does it mean for global climate politics? This article investigates the profiles of youth participants in global climate politics to answer these questions. We define and analyze three potential youth climate elite groups: positional, decisional and reputational. We then examine whether individuals from these elite groups and/or their socio-demographic characteristics overlap. Our results show that no unique transnational youth climate elite exists. Most of all, more than elite or non-elite, we reveal the power hierarchies that persist regarding how youth is understood in global climate politics, at the detriment of a more inclusive and ambitious climate agenda.
Publisher Copyright: © 2025 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: climate COPs; Decisional elite; Greta Thunberg; positional elite; reputational elite; youth representation